Self Made Nostril Retainer - Raymond, Benni; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
The main feature of the unilateral cleft lip nasal deformity is the asymmetry of the nose compared with the non cleft side. Nasal stents or nostril retainers are suggested to be useful in the management of these patients in order to maintain the new morphology and to mold the shape during healing process. To date, there are many types of factory made nostril retainer, but the price is relatively expensive and in contrary, most of our patient came from low-income population. The idea is to provide an easy and practical nostril retainer to obtain, easy to manufacture and easy to apply preoperatively and postoperatively, and it is also cost effective. Primary nose model including the nasal cavity is designed on the basis of non cleft side of patient’s nose. It is made by injecting alginate as negative impression. We use gypsum powder as positive impression material. From that positive impression, we mirror it to create other side of the nostril. Nostril retainer is then made using home-use silicone gel. We postulate that by using self-made nostril retainer which is made using cheap material. All of our patients could afford one, because the use of nostril retainer has been found effective post operatively after cleft primary rhinoplasty, avoiding relapse of the nasal reconstruction and drop of the nasal ala.